ANALISIS FAKTOR-FAKTOR PENYEBAB MEROKOK PADA MAHASISWA FKIP UNTAN PONTIANAK TAHUN AJARAN 2019/2020 - Hadi Tomi; Yuline Yuline; Luhur Wicaksono (Universitas Tanjungpura, 2021)
AbstractThis study aims to describe and find out about the Characteristics, Factors that cause smoking, and any Impact that arises on FKIP UNTAN Pontianak students in the academic year 2019/2020. This research method is a descriptive method with a form of survey research. The population in this study is an active student of FKIP UNTAN Pontianak academic year 2019/2020 class 2017 which is a total of 69 male students. This study uses a quantitative approach with indirect communication data collection techniques, and the data collection tools used are questionnaires. Based on the results of this study shows that the factors that cause smoking in FKIP UNTAN Pontianak students in the academic year 2019/2020 are in the category